Climate tipping and economic growth: precautionary capital and the price of carbon - Van der Ploeg, R; de Zeeuw, A (University of Oxford, 2013)
The optimal reaction to a climate tipping point which becomes more imminent with global warming is to be precautionary in accumulating additional capital to curb the adverse effects of the calamity and to price carbon to make catastrophic change less imminent. However, if the mean lag for impact of the catastrophe is long enough, the additional saving response will be smaller and can turn negative. We also decompose the optimal carbon price into its catastrophe components and a conventional marginal damages component, and show the separate effects of relative intergenerational inequality aversion and relative risk aversion using Duffie-Epstein preferences. Focusing on a productivity catastrophe, we calibrate our model and show how sensitive the policy responses are to the degrees of intergenerational inequality aversion and risk aversion, the trend rate of economic growth, the hazard rates, and how long it takes for the catastrophe to have its full impact.